2005
DOI: 10.4028/www.scientific.net/kem.284-286.35
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hydroxyapatite on the Remineralization of Dental Fissure Sealant

Abstract: The purpose of this study is to investigate the remineralization of enamel in the human tooth by fissure sealant containing various amount of hydroxyapatite. Prior to remineralization experiments, the necessary requirements of the dental fissure sealant, the curing depth and the curing time, were measured with the content of the hydroxyapatite according to the standard of ISO 6874. Various amount of hydroxyapatite was mixed uniformly using sonicator up to 20 wt% to the fissure sealant. In spite both the curing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…These zones were resultant from the precipitation of Ca, P and F into HA in these areas. These findings were in accordance with Park et al, [ 15 ] and Choudhary et al [ 23 ]. Both studies concluded that these zones were remineralization zones because there were no similar signs in the control group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These zones were resultant from the precipitation of Ca, P and F into HA in these areas. These findings were in accordance with Park et al, [ 15 ] and Choudhary et al [ 23 ]. Both studies concluded that these zones were remineralization zones because there were no similar signs in the control group.…”
Section: Discussionsupporting
confidence: 93%
“…The qualitative changes at the tooth surface and at the tooth/sealant interface were observed at all designated stages for all groups as previously mentioned. The presence of either granular, globular or white zones at the interface was considered positive for remineralization [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…There was no synergistic effect of fluoride on remineralization in this vitro study. It was expected that the remineralization effect would be more pronounced when the fluoride ions of the toothpaste interact with calcium and phosphate ions in saliva [7]. Therefore, a future study will evaluate the synergic effect of fluoride by adding calcium and phosphate ions into the tooth slurry.…”
Section: Resultsmentioning
confidence: 99%